From supply chain to demand chain: the role of lead time reduction in improving demand chain performance - de Treville, Suzanne; Shapiro, Roy D; Hameri, Ari‐Pekka (Journal of Operations Management, 2004)
AbstractTo improve demand chain performance, is it better for parties in a supply chain to focus first on lead time reduction, or instead concentrate on improving the transfer of demand information upstream in the chain? Even though the theory of supply and demand chain management suggests that lead time reduction is an antecedent to the use of market mediation (i.e., adjusting production to fit actual customer demand as it materializes) [Harvard Business Rev. 75 (2) (1997) 105] to reduce transaction uncertainty in the chain, which can be conceptualized as the primary goal of supply chain management [J. Operat. Manage. 11 (3) (1993) 289], demand chain parties often are observed in practice to begin with information transfer improvement, ignoring the problem of long lead times. In this paper, we propose a framework for prioritizing lead time reduction in a demand chain improvement project, using a typology of demand chains to identify and recommend trajectories to achieve desirable levels of market mediation performance.